HUBUNGAN ANTARA DISPOSISI MATEMATIS DAN KEMAMPUAN KOMUNIKASI MATEMATIS DALAM MATERI STATISTIKA DI SMA - Riyani, Ade; Jami?ah, Yulis; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe the relationship between mathematical disposition and mathematical communication ability of students in statistics subject at BAWARI Islamic High School Pontianak. The research method used is a correlation research method with a form of qualitative research. The subjects in this research are six students from science class and the results of the research is student answer sheets from the results of tests of mathematical communication ability, mathematical disposition questionnaires and interview results. The results showed that students' oral mathematical communication skills were classified as poor, students were only able to meet one indicator. Students' written communication skills are not good, students are only able to fulfill the indicators of writing ideas as a form of solving statistics problems, the other two indicators have not been fulfilled. Five students had a positive disposition and one student had a very positive disposition. The relationship between mathematical disposition and mathematical communication skills is not concomitant. The facts in the field show that not always students who have a positive mathematical disposition have good mathematical communication skills too. This can be influenced by several factors, namely: from instrument factors, student factors and learning factors. Keywords: Mathematical Disposition, Mathematical Communication Ability, Statistics